Spermatic and testicular damages in rats exposed to ethanol: Influence of lipid peroxidation but not testosterone - Siervo, Glaucia E. M. L.; Vieira, Henrique R.; Ogo, Fernanda M.; Fernandez, Carla D. B. [UNESP]; Goncalves, Gessica D.; Mesquita, Suzana F. P.; Anselmo-Franci, Janete Ap.; Cecchini, Rubens; Guarnier, Flavia A.; Fernandes, Glaura S. A. (Elsevier B.V., 2015)
Chronic consumption of ethanol causes morphological and physiological changes in the reproductive system of mammals. Vitamin C has an antioxidant role in organisms by neutralizing the ROS (reactive oxygen species) produced by oxidizing agents and this vitamin has an important function in the male reproductive system. The aim of this study was to evaluate whether vitamin C could prevent or attenuate the alterations in the male reproductive system caused by ethanol consumption. To test this hypothesis, male rats were divided into three experimental groups and treated by gavage for 63 days. The ethanol (E) and ethanol +vitamin C (EC) groups received 2 g/kg of ethanol (25% v/v) daily. In addition to ethanol, the EC group received vitamin C at a dose of 100 mg/day, diluted in water. The control group (C) received only the vehicle. On the 64th experimental day, the animals were anesthetized and euthanized, and blood was collected for plasmatic hormonal analysis. The testis, epididymis, vas deferens, and seminal vesicles were removed and weighed. Sperm from the vas deferens was submitted to morphological and motility analysis. The testis and epididymis were used for oxidative stress and histopathological analysis, sperm count, morphometric analysis of the testis, and stereological analysis of the epididymis. The results showed that vitamin C has a protective effect in the testes of adult male rats, entirely normalizing the parameters of sperm count, spermatogenesis kinetics, lipid peroxidation levels, and sperm motility, as well as partially normalizing the histopathological damage in the testis, epididymis, and sperm morphology. Thus, we concluded that lipid peroxidation is a major mechanism by which ethanol affects the testes and sperm, whereas no plasmatic testosterone alterations were found.
Keywords: Testis; Epididymis; Sperm; Ethanol; Vitamin C; Lipid peroxidation